2021
DOI: 10.1371/journal.pone.0253539
|View full text |Cite
|
Sign up to set email alerts
|

Capacity building of healthcare workers: Key step towards elimination of viral hepatitis in developing countries

Abstract: Background Lack of awareness about viral hepatitis (VH) potentially predisposes the healthcare workers (HCWs) to a higher risk of infection and may in turn increase the risk of transmission of the infection to their families and in the community. Thus, combating VH, requires adequate and updated training to the HCWs. With this objective, Project PRAKASH designed a meticulously planned training program, aimed to assess the effect of a one-day training on VH among in-service nurses. Methods and material The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…[ 24 ] Nurses working in the clinical areas were found to have better knowledge as compared to student nurses (OR3.25, CI 1.95-5.39, P = 0.001). In line with a study,[ 14 ] those employed in government sector had better knowledge than those in private sectors (OR 1.42, CI 1.19-1.68, P = 0.001). Additionally, nurses who had ever been trained or informed on post-exposure prophylaxis protocol had better knowledge (OR 1.37, CI 1.08-1.74, P = 0.009), as did those who were provided informational material on specific waste disposal in their health facilities (OR 1.83, CI 1.10-3.04, P = 0.02).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…[ 24 ] Nurses working in the clinical areas were found to have better knowledge as compared to student nurses (OR3.25, CI 1.95-5.39, P = 0.001). In line with a study,[ 14 ] those employed in government sector had better knowledge than those in private sectors (OR 1.42, CI 1.19-1.68, P = 0.001). Additionally, nurses who had ever been trained or informed on post-exposure prophylaxis protocol had better knowledge (OR 1.37, CI 1.08-1.74, P = 0.009), as did those who were provided informational material on specific waste disposal in their health facilities (OR 1.83, CI 1.10-3.04, P = 0.02).…”
Section: Discussionsupporting
confidence: 88%
“…The overall knowledge about viral hepatitis among majority of nursing professionals (99.2%) was inadequate (poor-moderate). Most published surveys showed that knowledge about the diseases is sparse[ 14 ]: study among 4920 nurses showed lack of awareness of various aspects of hepatitis; another reported average knowledge among nurses. [ 15 ] Several other studies[ 16 17 18 19 20 21 22 23 ] too documented that various HCPs lacked adequate knowledge about viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published data on certain workshops trainings [ 26 , 47 , 49 56 ] indicate that the curricula were generally comprehensive, covering epidemiology, diagnosis, workup, and treatment of HBV, HCV, or both. We highlight two specific trainings, the WHO Southeast Asia and Western Pacific regional training [ 57 ] and the Institute of Liver and Biliary Sciences “Hepatitis Induction Program” for nurses [ 58 ] Tables 5 , 6 , 7 , 8 and 9 .…”
Section: Resultsmentioning
confidence: 99%